Complete form of pachydermoperiostosis in a 16-year-old boy: A case report - Sahana M Srinivas; Suman Swamynathan; Vani Hebbal Nagarajappa; Raghupathy Palany (Wolters Kluwer Medknow Publications, 2022)
Pachydermoperiostosis is an inherited osseocutaneous disorder. The unusual increased levels of prostaglandin E2 due to mutations in either HPGD gene or SLCO2A1 gene are regarded as the causative factor. Our case report is about a 16-year-old boy who presented with cutis verticis gyrata, clubbing of digits, arthralgia, seborrhea, acne vulgaris, blepharoptosis, macrocheilia, column-like legs, and periosteal thickening in all long bones of the extremities characteristic of complete form of pachydermoperiostosis. No effective treatment has been proposed for this condition. Hence, counseling the child and parents about the disease progression, detecting the complications, and efficaciously managing them will be the mainstay of the treatment.